(untitled) (Gaceta Técnica, 2014)
The main objective of this work is to analyze the distribution of urban facilities in Maracaibo’s health area. To achieve this, direct observation and contrast related to inherent regulations and materials of urban facilities were needed. These show the differences between which is observed and regulated. According to its nature and characteristics, the methodology required bibliographic inquiry and regulations to provide the interpretive critical synthesis of the information gathered by contrast. As a result, it concludes that there is not an adequate distribution of urban facilities in the health area specifically in Maracaibo, Zulia State. Venezuela. As a strategic proposal, guidelines and recommendations are included